2015
DOI: 10.1111/jam.12883
|View full text |Cite
|
Sign up to set email alerts
|

Alternative treatment of vaginal infections - in vitro antimicrobial and toxic effects of Coriandrum sativum L. and Thymus vulgaris L. essential oils

Abstract: To examine EOs as possible constituent of naturally based antimicrobial agents in vaginaletes for safety gynaecological application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
3
26
2
1
Order By: Relevance
“…The EOs tested in this study showed the presence of significant amounts of monoterpenes, mainly represented by thymol, α-pinene, and linalool compounds, in accordance with previous published data even if with different percentile [21] (Table 2). Carvacrol and thymol exerted an interesting anti-Candida in vitro activity both by BM and VC, similar to previous findings [2224], even against fluconazole-resistant C. glabrata and C. tropicalis strains. α-pinene showed a better activity by BM than VC; conversely, linalyl acetate showed the lowest activity against all strains tested both by two methods.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The EOs tested in this study showed the presence of significant amounts of monoterpenes, mainly represented by thymol, α-pinene, and linalool compounds, in accordance with previous published data even if with different percentile [21] (Table 2). Carvacrol and thymol exerted an interesting anti-Candida in vitro activity both by BM and VC, similar to previous findings [2224], even against fluconazole-resistant C. glabrata and C. tropicalis strains. α-pinene showed a better activity by BM than VC; conversely, linalyl acetate showed the lowest activity against all strains tested both by two methods.…”
Section: Resultssupporting
confidence: 91%
“…However, some data suggest that components presented in small amounts in EOs, such as carvacrol, also could play an important role in antimicrobial activity due to the possible synergistic action with other components [24, 25, 32, 33]. …”
Section: Resultsmentioning
confidence: 99%
“…brine shrimp test Corchorus capsularis 217 The cytotoxicity of the plant was investigated by brine shrimp lethality bioassay which revealed that coriander LC50 was 2.25 mg/ml. brine shrimp test Coriandrum sativum 218 Among the extracts of the plant root, leaf and stem ,the ethyl acetate extract of Coriandrum sativum roots showed the highest antiproliferative activity on MCF-7 cells (IC50 = 200.0 ± 2.6 μg/ml).…”
Section: -216mentioning
confidence: 99%
“…Coriandrum leaves have been reported to have antidiabetic, anti ulcer, anti-arthritic and several other medicinal uses [10]. Studies showed that Coriandrum leaves extract has anticancer activity [11]. Studies also showed that reversal of memory deficit in mice model is possible using Coriandrum leaves extract [12].…”
Section: Introductionmentioning
confidence: 97%